Transcriptomic Profiling of Intracranial Arteries in Adult Patients With Moyamoya Disease Reveals Novel Insights Into Its Pathogenesis - Xu, Shuangxiang; Wei, Wei; Zhang, Feiyang; Chen, Tongyu; Dong, Lixin; Shi, Jichun; Wu, Xiaolin; Zhang, Tingbao; Li, Zhengwei; Zhang, Jianjian; Li, Xiang; Chen, Jincao (Frontiers in Molecular Neuroscience, 2022)
Moyamoya disease (MMD) is a rare progressively steno-occlusive cerebrovascular disorder with unknown etiology. Here, we revealed the gene expression profile of intracranial arteries in MMD via RNA-seq. We identified 556 differentially expressed genes (DEGs) for MMD, including 449 and 107 significantly up- or down-regulated genes. Comparing with atherosclerosis associated intra-cranial artery stenosis/occlusion (AS-ICASO) controls, up-regulated genes were mainly involved in extracellular matrix (ECM) organization, whereas down-regulated genes were primarily asso-ciated with mitochondrial function and oxidative phosphorylation in MMD. Moreover, we found that a separate analysis of sex uncovers more DEGs (n = 1022) compared to an analysis of sex combined in MMD. We identified 133 and 439 sex-specific DEGs for males or females in MMD, respectively. About 95.6% of sex-specific DEGs were protein-coding genes and 3% genes belonged to lncRNA. Sex-specific DEGs were observed in all chromosomes, of which 95.49% and 96.59% were autosomal genes in males or females respectively. These sex-specific DEGs, such as AQP4, SOD3 and NR4A1, may contribute to the sex difference in MMD. This transcriptomic study high-lighted ECM and mitochondrial function as central molecular mechanisms underlying MMD, and revealed sex difference of gene expression in intracranial arteries, thereby providing new insights into the pathogenesis of MMD.